In Situ Ag Nanoparticles Reinforced Pseudo‐Zn–Air Reaction Boosting Ag2V4O11 as High‐Performance Cathode Material for Aqueous Zinc‐Ion Batteries. Issue 12 (11th November 2019) - Li, Qian; Liu, Yuyi; Ma, Kaixuan; Yang, Gongzheng; Wang, Chengxin
Abstract: Aqueous zinc‐ion batteries (AZIBs), which are low‐cost and environmentally friendly, have been regarded feasible for large‐scale energy storage. But the widespread application of AZIBs is hindered by lack of suitable cathode materials with high capacity and long cycle life. The zinc‐storage mechanisms, especially the formation of basic zinc salt (BZS), are still unclear. Here, Ag2 V4 O11 is developed as a cathode material for AZIBs, which delivers a specific capacity of 213 mA h g −1 and excellent cycling performance (93% capacity retention after 6000 cycles). The reversible formation/decomposition of BZS and reduction/oxidation of metallic Ag are ascertained during the insertion/extraction of Zn(H2 O)6 2+ . Remarkably, the phase composition of BZS in Zn(CF3 SO3 )2 ‐based electrolyte is identified first. The role of in situ formed Ag nanoparticles is simulated by employing the commercial Ag nanoparticles as an additive into the V2 O5 ‐based electrodes. The introduction of Ag significantly improves the specific capacity (at least 50% improvement) and accordingly it is proposed that the pseudo‐Zn–air reaction (oxygen reduction reaction‐like redox reaction happens on material surface in a closed system) promotes the electrochemical performance of Ag2 V4 O11 . This work reveals the BZS rather than unknown new phases on the electrode surface and puts forward a possible way in raising electrochemical properties by utilizing the pseudo‐Zn–air reaction. Abstract : A schematic of an electrochemical mechanism of Ag2 V4 O11 is illustrated. Upon discharge, Ag nanoparticles are detected stripping out to the surface of the materials. The Zn 2+ intercalation and pseudo‐Zn–air reaction take place simultaneously, while both together contribute to high capacity retention of 95% after 500 cycles at a current rate of 1 A g −1 .